When Social Media Marketing Drives Loyalty: the Moderating Role of Platform Usage Intensity on Brand Trust and Brand Equity in Traveloka - Juniarty Juniarty; Rosni Rosni (Jurnal Publikasi Ilmu Manajemen, 2026)
This study examines the effects of social media marketing activities on brand trust, brand equity, and brand loyalty among Traveloka users, and tests whether platform usage intensity strengthens the relationships between social media marketing and brand trust and brand equity. A quantitative causal design was applied through an online survey using purposive sampling. Eligible respondents followed Traveloka’s official social media, had used the appication within the previous 12 months, completed at least three travel-related transactions during that period, and regarded Traveloka as their primary travel platform. A total of 401 valid responses were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4 and a disjoint two-stage approach for the reflective-reflective higher-order construct. The results show that social media marketing positively and significantly affects brand trust, brand equity, and brand loyalty. Brand trust positively affects brand equity and brand loyalty, while brand equity also improves brand loyalty. Platform usage intensity significantly strengthens the effects of social media marketing on brand trust and brand equity. The findings extend the social media branding literature by identifying platform usage intensity as an important boundary condition and imply that Traveloka should combine high-quality social media content with sustained platform engagement to reinforce trust, brand value, and loyalty.